The effectivity of toothpick tooth brushing method on plaque control - Chiquita Prahasanti; Iwan Ruhadi; Agus Sobar Mulyana (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Periodontal diseases are associated with bacteria species which present in biofilms that colonize on dental surfaces. Several tooth brushing methods had been known and proved to be effective in maintaining oral hygiene. Among them, tooth pick technique was a relatively new method and its superiority in removing interproximal plaque was better than other methods. Purpose: The purpose of this study was to examine the effectivity of toothpick tooth brushing method to conventional method on periodontal health. Methods: This research was designed as an analytical observational study. Thirty samples selected from five hundred and twelve males Indonesian Air-force members in Malang, aged 18–40 yrs, with periodontal pockets (≤ 5 mm) in upper or lower teeth, without crowding, gingival index minimal > 1 (moderate gingivitis), OHI-S score minimal ≥ 1.3 (moderate), without systemic diseases, do not undergone medical therapy/drug prescriptions, without using mouth rinse during study, and without prosthesis. There were thirty samples in this research and devided to two groups, fifteen samples easch. The groups were toothpick tooth brusing method and conventional method (control group). In this study oral hygiene index simplified (OHI-S), gingival index (GI), bleeding on probing (BOP) and pocket depth were examined. Results: There were significant differences (p = .001) in OHI-S, GI, BOP, and PD before and after conducting each toothbrushing method, as well as differences between means (quarrel means), that were p = .003; p = .001; p = .001 and p = .001 consecutively. Conclusion: Toothpick brushing method was more effective in plaque control compared to conventional method.Latar belakang: Penyakit periodontal berhubungan dengan bakteri yang berkoloni dalam biofilm yang terdapat di permukaan gigi. Saat ini telah dikenal berbagai macam metode menyikat gigi tetapi masih belum ada penelitian tentang efek metode tersebut terhadap OHI-S. Penelitian in ingin menunjukkan efek menyikat gigi dengan metode toothpick terhadap kesehatan jaringan periodontal. Tujuan: Tujuan dan penelitian ini adalah untuk mengetahui efektivitas metode toothpick dibandingkan metode konvensional dalam kontrol plak. Metode: Jenis penelitian ini adalah analitik observasional. Sampel sejumlah tiga puluh orang diseleksi dari 512 anggota TNI Angkatan Udara Skadron Pasukan Khas 464 Wing II Lanud Abdulrahman Saleh Malang, usia 18–40 tahun, dengan kedalaman poket periodontal (≤ 5 mm) pada gigi rahang atas/bawah dengan, susunan gigi yang tidak berdesakan, memiliki skor gingival indeks minimal > 1 (gingivitis sedang), memiliki skor OHI-S minimal ≥ 1,3 (sedang), tanpa ada kelainan sistemik, tidak dalam perawatan dokter/mengkonsumsi obat-obatan, tidak menggunakan obat kumur selama penelitian, tidak menggunakan protesa. Sampel dibagi menjadi dua kelompok, lima belas orang menggunakan metode toothpick sedangkan lima belas orang menggunakan metode konvensional sebagai kelompok kontrol. Hasil: Terdapat perbedaan yang bermakna (p = .001) pada OHI-S, GI, BOP dan kedalaman poket sebelum dan sesudah menyikat gigi dengan masing-masing metode menyikat gigi yang ditetapkan. Selain itu, terdapat perbedaan bermakna antara selisih rerata sebelum dan sesudah menyikat gigi (p = .003; p = .001; p = .001 and p = .001) antara kedua kelompok tersebut. Kesimpulan: Metode toothpick brushing lebih efektif uuntuk kontrol plak dibanding dengan kelompok kontrol.